The Effect of Product Quality, Personal Seling and Certification on The Desicion to Purchase Oriflame Products in Yogyakarta - Khasanah, Uswatun; Salam, Abdul; Wibowo, Febrian Wahyu; Kamal, Al Haq (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze the influence of product quality, personal selling, and halal certification on purchasing decisions of Oriflame products in Bantul, Yogyakarta. . This research uses the Theory of Planned Behavior (TPB) and Theory of Reasoned Action (TRA) theoretical approaches. This research uses a quantitative method with a questionnaire, involving 100 respondents selected using the Lemeshow formula. Independent variables include product quality (X1), personal selling (X2), and halal certification (X3), while the dependent variable is purchasing decisions (Y). Data analysis was performed using EViews 12 with normality tests, reliability, classical assumptions, multiple linear regression, T test, F test and R2 test. The results showed that the three independent variables had a positive effect on purchasing decisions, with an Adjusted R² value of 82%, while 18% was influenced by other factors not mentioned in this study.